7DAYS Corporation / Shamim Shahira Abdul Aziz - Abdul Aziz, Shamim Shahira (2020)
7DAYS Corporation is a pen company with multipurpose function. This company was founded in January 2020, by Shamim Shahira binti Abdul Aziz. 7DAYS Corporation has plants that manufacture its products located in Selangor. Location of the company is located on the outskirt of Bangi, Selangor which is near the manufacturing factory and raw materials suppliers. With the purpose of ensuring customer’s satisfaction towards the writing instrument and having better writing in their daily life, 7DAYS Corporation has come up with new technology innovation. 7DAYS Corporation is also concerned about the environment. Thus, we made pen with technology which customer only need to refill the ink of the pen and liquid paper correction, instead of buying the whole new pen again. This is to help reduce wastage and protect the environment. 7DAYS Corporation has always delivered good quality product and service to our customers. 7DAYS Corporation has expanded the distribution line to include both wholesalers to retailers, allowing consumers to easily purchase 7DAYS pen in the market. Until today, 7DAYS Corporation is continuously delivering the best quality of writing instruments and services to meet the prospective needs and requirements of today's consumers.